Management of cardiac trauma and penetrating cardiac injuries with severe hemorrhagic shock: a 5-year experience - Tran Thuc Khang (Journal of Trauma and Injury)
Purpose The diagnosis and management of cardiac trauma and penetrating cardiac injuries pose significant challenges in emergency settings due to the rapid onset of life-threatening complications. This paper presents a narrative review to better describe the etiology, presentation, and management of penetrating cardiac trauma, offering insights and experiences related to performing emergency surgery for such cases. Methods We compiled cases of traumatic cardiac rupture and penetrating cardiac injuries accompanied by severe hemorrhagic shock that necessitated emergency surgery. Data were collected regarding the type of injury, causative agents, specific clinical features observed during emergency admission, intraoperative parameters, and treatment outcomes. Results Twenty-one patients (16 men, 5 women) with cardiac rupture or penetrating cardiac injuries were recorded. All patients presented in severe shock, and six cases (28.6%) experienced cardiac arrest upon arrival in the operating room. Cardiac rupture due to blunt chest trauma occurred in two cases (9.5%), and one case (4.8%) involved right atrial perforation due to complex open chest trauma. Penetrating injuries accounted for cardiac perforation in 18 cases (85.7%). Associated injuries were present in 11 cases (52.4%). The intraoperative mortality rate was 9.5%, and there was one postoperative death on the 11th day due to multiorgan failure. Conclusions Cardiac trauma and penetrating injuries are usually fatal unless promptly diagnosed and surgically treated. The timing and rapidity of emergency surgery—often foregoing ancillary tests and administrative procedures—are critical for patient survival. Emergency sternotomy, swift control of bleeding, and aggressive resuscitation are essential operative measures in saving lives. Factors that influence prognosis include the extent of blood loss, duration of cardiac arrest, acid-base imbalances, coagulopathy, multiorgan failure, and postoperative infections.